2019
DOI: 10.3892/ijmm.2019.4437
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of Pdk1 contributes to primordial follicle activation via the upregulation of YAP expression and the pro‑inflammatory response

Abstract: The molecular mechanisms underlying the activation of primordial follicles are poorly understood. The serine/threonine protein kinase phosphoinositide-dependent kinase 1 (PdK1), a pivotal downstream effector of phosphatidyl inositol-3 kinase (PI3K) signaling, plays a vital role in cellular signaling. In order to identify the function of PdK1 in ovarian follicle development, this study used conditional Pdk1 deletion in mouse oocytes by crossing Pdk1 loxP/loxP mice with transgenic mice carrying Gdf-9 promoter-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
(29 reference statements)
0
8
0
Order By: Relevance
“…Study demonstrated expression of Hippo signaling pathway genes and shows that ovarian fragmentation increases actin polymerization, leads to YAP nuclear translocation and promotes follicular growth in mammalian ovaries (22). Further studies have shown that enhanced YAP expression and increased proin ammatory responses also contribute to the activation of massive primordial follicles (42). Previous studies showed that Hippo signaling pathway was mainly involved in the regulation of ovarian fragmentation which means that ovarian development is closely related to the Hippo pathway (43).…”
Section: Discussionmentioning
confidence: 94%
“…Study demonstrated expression of Hippo signaling pathway genes and shows that ovarian fragmentation increases actin polymerization, leads to YAP nuclear translocation and promotes follicular growth in mammalian ovaries (22). Further studies have shown that enhanced YAP expression and increased proin ammatory responses also contribute to the activation of massive primordial follicles (42). Previous studies showed that Hippo signaling pathway was mainly involved in the regulation of ovarian fragmentation which means that ovarian development is closely related to the Hippo pathway (43).…”
Section: Discussionmentioning
confidence: 94%
“…As one of the most important signaling pathways, the Hippo signaling pathway plays an important role in regulating female reproductive system development (45)(46)(47). Yuan Cheng and colleagues first demonstrated the ability of actin polymerizationpromoting drugs to inhibit the Hippo signaling pathway and promote organ growth, and showed that disruption of Hippo signaling in ovarian follicles can be used for infertility treatment, and in mammals, the Hippo pathway has four core components, including the serine/threonine kinase MST1/2 (homologue of Hippo/ Hpo) (48,49). YAP is a transcription factor that enters the nucleus following phosphorylation and may play a role in the transition from primordial to primary follicles.…”
Section: Discussionmentioning
confidence: 99%
“…In mouse placenta, BPA causes a decrease in the labyrinthine and spongiotrophoblast zone proportions with narrowing of the intervillous spaces [34][35][36][37]. The exact mechanisms as to how this occurs seems to be debatable; matrix metalloproteinase-2/9 (MMP2/MMP9) seems to be involved, but upregulation or downregulation occurs depending on the model used [34,35,38,39].…”
Section: Effects Of Bisphenols On the Placentamentioning
confidence: 99%
“…BPA inhibits basal and vascular endothelial growth factors (VEGF) by downregulating mRNA expression of VEGF and lowering CpG methylation of gene promoters associated with oxidative stress in HTR8/SVneo cells [42,43]. Decreased migration and attachment have also been observed across a wide range of concentrations, which limit the optimal invasion necessary for sufficient placental formation [24,26,35,38]. Overall, the resulting gradual uteroplacental insufficiency from suboptimal placentation may provide inadequate oxygenation that can trigger eventual feto-maternal stress.…”
Section: Effects Of Bisphenols On the Placentamentioning
confidence: 99%